1986
DOI: 10.1038/bjc.1986.57
|View full text |Cite
|
Sign up to set email alerts
|

The differential cytotoxicity of RSU 1069: Cell survival studies indicating interaction with DNA as a possible mode of action

Abstract: Summary The hypoxic cell radiosensitizer RSU 1069 (1-(2-nitro-1-imidazolyl)-3-(1-aziridinyl)-2-propanol) shows, on a concentration basis, a 100-fold greater toxicity towards hypoxic relative to aerobic cells. This toxicity is substantially greater than that of misonidazole, a compound of similar electron affinity. Reductive processes are important for hypoxic toxicity; this is demonstrated by the fact that misonidazole, in excess, can protect against the hypoxic but not aerobic toxicity of RSU 1069. The import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
10
0

Year Published

1986
1986
1990
1990

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…Reduced blood flow in tumours can cause lowering of the oxygen status of the tumour, thereby causing radiation resistance (Kruuv et al, 1967). This so-called 'stealing' effect has recently been exploited by Chaplin and Acker (1987) in order to increase the anti-tumour effect of the bio-reductive agent, RSU 1069 (Adams et al, 1984) a compound which is activated under hypoxic conditions to give a species 100 x more toxic than the parent compound (Stratford et al, 1986).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced blood flow in tumours can cause lowering of the oxygen status of the tumour, thereby causing radiation resistance (Kruuv et al, 1967). This so-called 'stealing' effect has recently been exploited by Chaplin and Acker (1987) in order to increase the anti-tumour effect of the bio-reductive agent, RSU 1069 (Adams et al, 1984) a compound which is activated under hypoxic conditions to give a species 100 x more toxic than the parent compound (Stratford et al, 1986).…”
mentioning
confidence: 99%
“…Reduced blood flow in tumours can cause lowering of the oxygen status of the tumour, thereby causing radiation resistance (Kruuv et al, 1967). This so-called 'stealing' effect has recently been exploited by Chaplin and Acker (1987) in order to increase the anti-tumour effect of the bio-reductive agent, RSU 1069 (Adams et al, 1984) a compound which is activated under hypoxic conditions to give a species 100 x more toxic than the parent compound (Stratford et al, 1986).Reduction of blood flow in tumours may also be potentially useful for enhancing the effects of some anti-cancer drugs. The rationale for this is that, administration of the vaso-active drug at the time at which the chemotherapeutic agent has reached its maximum tumour concentration, will inhibit loss of active drug from the tumour.…”
mentioning
confidence: 99%
“…It is thought to act as a monofunctional alkylating agent (aziridine group) under normoxic conditions and under hypoxic conditions as a bifunctional alkylating group through the aziridine group and the reduced nitro group (Stratford et al, 1986). As a hypoxic-cell cytotoxin it is 100 times more toxic to anoxic than to normoxic cells in vitro (Ahmed et al, 1986;Stratford et al, 1986). In a limited clinical trial it has been found to cause the side-effects of nausea and vomiting (Horwich et al, 1986).…”
mentioning
confidence: 99%
“…RSU 1069 (1-(2-nitro-1-imidazolyl)-3-(1-aziridinyl)-2-propanol) is a MISO analogue in which an aziridine group replaces the methoxy group in the Nl sidechain (Adams et al, 1984). It is thought to act as a monofunctional alkylating agent (aziridine group) under normoxic conditions and under hypoxic conditions as a bifunctional alkylating group through the aziridine group and the reduced nitro group (Stratford et al, 1986). As a hypoxic-cell cytotoxin it is 100 times more toxic to anoxic than to normoxic cells in vitro (Ahmed et al, 1986;Stratford et al, 1986).…”
mentioning
confidence: 99%
“…This compound has been shown to be selectively toxic to hypoxic cells both in vitro (Stratford et al, 1986a) and in vivo (Chaplin et al, 1986).…”
mentioning
confidence: 99%